Labor Market Impacts of the Green Transition: Evidence from a Contraction in the Oil Industry - Cloé Garnache; Elisabeth Isaksen; Maria Nareklishvili (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
The transition to a low-carbon economy requires a contraction of fossil fuel sectors, raising questions about the labor market costs of reallocation. We study the 2014 oil price shock as a natural experiment to examine the contraction of Norway's oil industry. Using matched employer–employee data, we estimate long-run effects on earnings and employment using two complementary approaches. A difference-in-differences design shows moderate losses for all oil workers, while an event study reveals substantially larger and more persistent losses among displaced workers–up to 10% in earnings and 5% in employment nine years after displacement, especially for those with lower educational attainment. Although few displaced workers transition into green jobs, they are equally likely to enter green and brown (non-oil) sectors when accounting for the size of each destination sector. Earnings losses are larger for those entering green jobs rather than brown (non-oil) jobs, but smaller than for those entering other sectors. Decomposition results indicate that differences in establishment wage premiums–rather than skill mismatch–explain most of the observed gaps.
Keywords: Q32; Q52; J24; J63; 330; green transition; oil industry; job displacement; distributional effects; establishment wage premium; skills mismatch